Unspoken Therapy: Dogs’ Contribution to Their Owners’ Well-being, Coping Mechanism, and Newfound Meaning in Life - Kazandjiev, Daisy T.; Medez, Sharon Rose G. (Philippine Social Science Journal, 2025)
For individuals living alone, the mental and emotional challenges of solitary life can be profound, yet they are often mitigated by the companionship of a dog. This study employed a qualitative, phenomenological approach to explore the lived experiences of solitary adult dog owners. Through unstructured interviews and Lichtman’s 3Cs analysis, the research revealed that dogs act as “four-legged therapists,” providing crucial support that enables owners to cope with challenges and rediscover life’s purpose. These findings underscore the therapeutic value of the human–animal bond and advocate for integrating dog-assisted therapy into academic, medical, and rehabilitation settings. As a preliminary step in addressing gaps in the literature, this study suggests that future research should extend to broader demographics and utilize quantitative methods. Ultimately, this work positions dog-assisted therapy as a credible intervention for enhancing well-being amidst the dynamic struggles of solitary living.